Blending of linseed oil with edible oil to improve nutritional quality of edible oil blends: Blending of linseed oil with edible oil to improve nutritional quality of edible oil blends - PRAMOD D FARDE,; MAHABALESHWAR V HEGDE,; ANAND A ZANWAR, (Journal of Oilseeds Research, 2023)
Per capita consumption of edible oils has significantly increased (Yadav et al., 2022). Deficiency of essential omega-3 fatty acid, altered omega-6 to 3 ratio and its impact on human health is well established (Simopoulos, 2002). Majority of the edible oil consumed in India are rich in omega-6 fatty acid, saturated fatty acids and have limited amount of omega-3 fatty acids. In order to improve omega 6:3 ratio, omega-3 fatty acid intake needs to be raised. Blending can effectively improve the omega-3 content and thereby omega-6 to 3 ratio (Joshi et al., 2022). However, maintaining the nutritional quality, long term storage and thermal stability of these blended oils is a major challenge.